Peningkatan Kompetensi Guru TK ABA di Kapanewon Pajangan, Bantul - Muhammad Eko Atmojo; Ridho Al-Hamdi; Vindhi Putri Pratiwi (Universitas Lancang Kuning, 2022)
The Covid-19 pandemic that has been going on since 2020 until now has brought many changes to several aspects. One of them is in the aspect of education, where school education is required to continue, and students can capture learning well. So, this requires good coordination between teachers, students, and parents to create learning success. During the Covid-19 pandemic, learning is carried out online and offline. However, online learning at the kindergarten level, teachers still have problems where online learning is still required to have professional competence. This is to keep creating interesting, innovative learning, able to create creativity that can be easily understood by kindergarten students. Therefore, to improve the competence of teachers, it is necessary to upgrade the skills possessed by kindergartens. The method used in this service is through the provision of training to teachers at the ABA TK Kapanewon Pajangan. This will later be used to improve competence in the field of Information Technology so that teachers can carry out online learning better and upgrade the skills of kindergarten teachers